PRODUCTIVITE TOTALE DES FACTEURS ET MODELES DE MESURE : choix judicieux de méthode d’analyse - MOBONDA, Ricky MOLOKO; AMUNDE , Francis ANYOLE; Y’ANGANDUA , Jules Karl MBAY (IJRDO - Journal of Business Management, 2021)
The difference with new economic growth theories hypothesis and the Solow theory of growth have provided a new methodology framework. This framework established the sustainable choice of parametric measure and non-parametric measure of total productivity of factors(TPF).Those choices which are depended to initial Solow hypothesis allow to release non-parametric analysis to parametric one. Especially, while time series datas or panel datas are used to set econometric method.For this relevant analysis, the GMM lag use TFP like endogenous variable.